Risks in Social Networks: Awareness of Future Law-Enforcement Officers - Butrimė, Edita; Zuzevičiūtė, Vaiva (Information & Media, 2018)
The main purpose of this article is to investigate the awareness of students, future law enforcement officers – who will be expected to protect other citizens – on the risks of their personal safety in the digital space. The paper presents both theoretical considerations and empiric data from a study (completed in 2016 and in 2017), dedicated to investigating whether future law enforcement students recognize the main risks for safety in digital space. This study is important in light of the fact that a large part of our contemporary social, personal and professional lives is being carried out in digital spaces. If future law enforcement officers are unable to recognize the risks on safety, they, as a consequence, will not be professional and ready enough to consult and provide support for citizens on the issues that begin, in some cases, to dominate the functioning of a contemporary person in a contemporary world.
Keywords: social network sites; risks in social networks; safety of personal data